Integrating Healing Centered Design Principles into Diagnostic and Laboratory Facility Planning - John Chinemerem Ogbete; AbuYusuf Aminu-Ibrahim; Obinna Chima Iwuanyanwu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Integrating healing-centered design principles into diagnostic and laboratory facility planning has gained increasing attention as healthcare systems recognize the influence of physical environments on patient experience, staff wellbeing, and clinical performance. Diagnostic and laboratory spaces are traditionally engineered for efficiency, biosafety, and regulatory compliance, often overlooking psychosocial factors that shape stress, trust, and cognitive functioning. This paper explores how healing-centered design can be systematically embedded within the planning and delivery of diagnostic and laboratory facilities without compromising technical rigor or safety standards. Drawing on interdisciplinary literature spanning healthcare architecture, environmental psychology, laboratory design, and health services research, the study synthesizes evidence on spatial configuration, lighting, acoustics, biophilic elements, wayfinding, and material choices. The analysis demonstrates that environments designed to reduce anxiety, enhance comfort, and support dignity can improve patient cooperation, diagnostic accuracy, and staff productivity while mitigating fatigue and error. Particular emphasis is placed on laboratory workflows, specimen collection areas, waiting zones, and staff workspaces where stress and cognitive load are highest. The paper further examines regulatory and operational constraints, highlighting strategies for aligning healing-centered features with infection prevention, biosafety, and quality assurance requirements. Case-informed insights illustrate how modular layouts, natural light integration, noise control, and culturally responsive design can be adapted to diverse health system contexts, including resource-constrained settings. A conceptual planning framework is proposed that integrates healing-centered objectives into early needs assessment, functional programming, stakeholder engagement, and post-occupancy evaluation. By reframing diagnostic and laboratory facilities as therapeutic environments rather than purely technical spaces, the study provides practical guidance for planners, architects, laboratory managers, and policymakers. The findings support a shift toward human-centered infrastructure that enhances diagnostic effectiveness, workforce resilience, and patient trust, while maintaining compliance, efficiency, and long-term operational sustainability. Such integration contributes to more compassionate, equitable, and high-performing diagnostic services capable of meeting growing clinical demand and evolving expectations for quality, safety, and holistic care delivery. Future research should evaluate outcomes using mixed methods, longitudinal metrics, and equity indicators, ensuring design decisions are evidence informed, scalable, and culturally grounded, while supporting regulatory compliance, technological adaptability, continuous learning, and measurable improvements in diagnostic quality and patient-centered system performance.